Weighted CTDI Equation for 3D Rotational Angiography: A Monte Carlo Study - Azzi, A.; Hidayat, R.; Rosa, A.; Lubis, L. E. (National Research and Innovation Agency, 2024)
This study aims to verify the weighted Computed Tomography Dose Index (CTDIw) coefficients of 3D rotational angiography (3DRA) procedure using Monte Carlo simulation. The Monte Carlo simulation EGSnrc usercode was employed for 3D dose simulations of the rotational angiography procedure. A virtual phantom resembles the head CTDI phantom was constructed, with a diameter of 16 cm and a density resembling polymethyl methacrylate (1.13 g/cm3). A series of virtual phantoms consisting of 5 images with ionization chamber detectors at the center position, 12 o'clock, 9 o'clock, 6 o'clock, and 3 o'clock were acquired. Simulations were performed with photon sources of 70 and 109 kVp for 200-degree x-ray tube rotation. The field of view was divided into narrow, wide, and full beam with diameters of 1.7 cm; 4.9 cm; and 8.6 cm, respectively. The simulated doses at the ionization chamber were processed into weighting factor for weighted CTDI and compared with direct measurements. The dose ratio between peripheral and center positions for 360° CBCT and 200° 3DRA was 1:1 and 1:3 in this study. The weighting factors for 3DRA were determined as CTDIcenter = ¼ and CTDIperiphery = ¾. The measured average percentage difference of CTDIw between our weighted factor and conventional CTDIw was 1.75 % (-3.99 % to 6.08 %). The x-ray tube position of 3DRA impacted the accuracy of weighting factor of CTDIw, with implications for the proposed weighting factor (Wcenter = ¼ and Wperiphery = ¾) when using a 3DRA machine.